Pengaruh Jenis Media terhadap Konsentrasi Biomassa dan Kandungan Protein Mikroalga Chaetoceros calcitrans - Trikuti, I Komang; Anggreni, A.A.M. Dewi; Wayan Gunam, Ida Bagus (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 4 No 2 (2016): Juni, 2016)
This study aims were to know the effect of media type on biomass concentration and protein content of microalgae Chaetoceros calcitrans and determine the best media type for production of microalgae Chaetoceros calcitrans with highest protein content of microalgae Chaetoceros calcitrans. This study was designed with randomized block design with single factor. The factor was media type consist of 5 types, namely NPSI media, Walne media, Guilard media, Na media, and Pertanian media. Each treatment was grouped into 3 based on time of cultivation. The data obtained were analyzed by analyzed of variance followed by least significant difference test, if a treatment had significant effect. The result showed that media type had very significant effect on the biomass concentration and protein content. The highest protein content was obtained from the microalgae Chaetoceros calcitrans which was cultivated in Pertanian media amounted of 41,92%. Key words: biomass, Chaetoceros calcitrans, media, protein.
Keywords: 93